The interplay between power structure and decision-making in supply chains: A systematic review - Nurhayati, Kartika; Rezaei, Jafar; Tavasszy, Lóránt (Journal of Supply Chain Management Science, 2021)
This study provides a systematic review of the literature and a conceptual framework of the interplay between power structure and supply chain decision-making. This systematic review studies 281 research papers published in peer-reviewed journals between the year 1994-2020 and uses content analysis and network visualization of major themes and keywords. Thematic analysis was conducted to examine growing discussion in the literature and to identify research gaps. The findings of this review highlight the component of power structure across business-to-business (B2B) relationships, including its impact on companies’ decision-making. Past literature indicates that power, originating from various sources, could be deliberately exploited and exercised by a company to influence the process and outcome of supply chain decisions. The findings demonstrate the mechanics of power and the prevalent domains of decision that are discussed in the organizational power literature: pricing, quality management, sustainability, alliance building, sourcing, investment, inventory, product development and power shifting efforts. The main contribution of this paper is that it provides a critical synthesis of the role of power structure in supply chain decision-making, identifying 7 novel themes and related future research avenues. For managers and decision-makers, this study helps to raise situational awareness to comprehend power structures among supply chain collaborators. This awareness may help managers to identify threats to and opportunities for future supply chain decisions.